Systematic review on measurement properties of questionnaires assessing the neighbourhood environment in the context of youth physical activity behaviour - Reimers, Anne Kerstin; Mess, Filip; Bucksch, Jens; Jekauc, Darko; Woll, Alexander (BMC Public Health, 2013)
Background: High-quality measurement instruments for assessing the neighbourhood environment are a prerequisite for identifying associations between the neighbourhood environment and a person’s physical activity. The aim of this systematic review was to identify reliable and valid questionnaires assessing neighbourhood environmental attributes in the context of physical activity behaviours in children and adolescents. In addition, current gaps and best practice models in instrumentation and their evaluation are discussed. Methods: We conducted a systematic literature search using six databases (Web of Science, Medline, TRID, SportDISCUS, PsycARTICLES and PsycINFO). Two independent reviewers screened the identified English-language peer-reviewed journal articles. Only studies examining the measurement properties of self- or proxy-report questionnaires on any aspects of the neighbourhood environment in children and adolescents aged 3 to 18 years were included. The methodological quality of the included studies was assessed using the COSMIN checklists. Results: We identified 13 questionnaires on attributes of the neighbourhood environment. Most of these studies were conducted in the United States (n = 7). Eight studies evaluated self-report measures, two studies evaluated parent-report measures and three studies included both administration types. While eight studies had poor methodological quality, we identified three questionnaires with substantial test-retest reliability and two questionnaires with acceptable convergent validity based on sufficient evidential basis. Conclusions: Based on the results of this review, we recommend that cross-culturally adapted questionnaires should be used and that existing questionnaires should be evaluated especially in diverse samples and in countries other than the United States. Further, high-quality studies on measurement properties should be promoted and measurement models (formative vs. reflexive) should be specified to ensure that appropriate methods for psychometric testing are applied in future studies.